The benefit of being still: energy savings during winter dormancy in fish come from inactivity and the cold, not from metabolic rate depression. Issue 1886 (5th September 2018) - Speers-Roesch, Ben; Norin, Tommy; Driedzic, William R.
Abstract : Winter dormancy is used by many animals to survive the cold and food-poor high-latitude winter. Metabolic rate depression, an active downregulation of resting cellular energy turnover and thus standard (resting) metabolic rate (SMR), is a unifying strategy underlying the persistence of organisms in such energy-limited environments, including hibernating endotherms. However, controversy exists about its involvement in winter-dormant aquatic ectotherms. To address this debate, we conducted simultaneous, multi-day measurements of whole-animal oxygen consumption rate (a proxy of metabolic rate) and spontaneous movement in a model winter-dormant marine fish, the cunner ( Tautogolabrus adspersus ). Winter dormancy in cunner involved a dampened diel rhythm of metabolic rate, such that a low and stable metabolic rate persisted throughout the 24 h day. Based on the thermal sensitivity ( Q 10 ) of SMR as well as correlations of metabolic rate and movement, the reductions in metabolic rate were not attributable to metabolic rate depression, but rather to reduced activity under the cold and darkness typical of the winter refuge among substrate. Previous reports of metabolic rate depression in cunner, and possibly other fish species, during winter dormancy were probably confounded by variation in activity. Unlike hibernating endotherms, and excepting the few fish species that overwinter in anoxic waters, winter dormancy in fishes, as exemplified by cunner, need not involve metabolic rate depression. Rather, energy savings come from inactivity combined with passive physico-chemical effects of the cold on SMR, demonstrating that thermal effects on activity can greatly influence temperature–metabolism relationships, and illustrating the benefit of simply being still in energy-limited environments.